Pengetahuan Dan Kefahaman Agama Dalam Kalangan Belia Melayu Di Lembah Kelang - Mashitah Sulaiman; Mohd Azmir Mohd Nizah; Marina Munira Abdul Mutalib; Roslizawati Mohd Ramly; Suhailiza Md. Hamdani; Mohd Nazir Ahmad; Khatijah Othman (Kolej Universiti Islam Antrabangsa Selangor, 2024)
Non-Indexed Publication